Negotiation of Gen Z Women's Identity in COD Practices: Between Domestic Space and the Digital Economy - Yulia Sukmana; Indra Novianto Adibayu Pamungkas; Arina Khairunisa (ETTISAL : Journal of Communication, 2026)
This study examines how Generation Z women in Bandung negotiate their financial autonomy and navigate risks through Cash on Delivery (COD) practices within the contemporary digital economy ecosystem. While existing literature often characterizes online cash reliance as a byproduct of limited technological adoption, this research challenges that assumption by exploring the intersection of digital access and financial security. The purpose of this study is to analyze the communicative construction of consumer identity and economic agency among Gen Z women by synthesizing Michael Hecht’s Communication Theory of Identity (CTI) with the framework of Feminist Economics. Utilizing a qualitative case study methodology, empirical data were gathered through semi-structured interviews with ten Generation Z female consumers selected via snowball sampling. The collected narratives were systematically evaluated using qualitative thematic analysis facilitated by NVivo software. The findings reveal that the preference for COD is not a sign of low digital literacy, but a sophisticated manifestation of risk awareness across CTI layers. At the individual and operational levels, informants perform tactical risk-mitigation behaviors such as store rating verification and review-searching to ensure financial control. Relationally and communally, these practices are embedded within domestic interdependence and distinct urban logistical networks, where consumers actively filter marketplace pressures and negotiate logistical coordination to claim financial sovereignty. Ultimately, this study contributes to digital sociology and communication studies by demonstrating how routine consumption practices operate as sites of tactical empowerment that reconfigure gendered power dynamics within the domestic sphere.